Correlation of TP53 and MDM2 Genotypes and Clinical Outcome in Platinum-Treated Head and Neck Cancer Patients with More than 10 Years' Follow-Up. Issue 2 (April 2016) - Vivenza, Daniela; Monteverde, Martino; Lattanzio, Laura; Tonissi, Federica; Astesana, Valentina; Denaro, Nerina; Comino, Alberto; Russi, Elvio; Lo Nigro, Cristiana; Merlano, Marco
Purpose: Adequate biomarkers are still required to optimize therapy in patients with locally advanced head and neck squamous carcinomas (HNSCC) treated with chemoradiotherapy (CRT). Methods: We updated the follow-up of 66 HNSCC patients treated with CRT we described more than 10 years ago, focusing on SNP Arg/Pro (R/P) at codon 72 and somatic mutations in TP53 and on SNP309 in the MDM2 gene. Results: In wild-type TP53 cases, overall survival (OS) was longer in 72RR and less favorable in 72PP (p = 0.005); when TP53 was mutated, OS was longest in 72PP and less favorable in 72RR and 72RP (p = 0.058). Median OS was significantly shorter in patients with MDM2 SNP309 GG or GT genotypes compared with the TT genotype (p = 0.002). Conclusions: TP53 SNP72 may be useful in selecting patients for CRT, but has to be related to somatic TP53 mutations. The MDM2 SNP309, easily determined in peripheral blood, might be more convenient as a predictive biomarker.